Early Childhood Learning Management: Multi-site Study in Pioneer Kindergarten and Matahari Bunda Kindergarten, Kurun District, Gunung Mas Regency - Wiwi, Wiwi; Aslamiah, Aslamiah; Noorhapizah, Noorhapizah (Formosa Journal of Science and Technology, 2025)
This study aims to reveal the management of early childhood learning in Perintis Kindergarten and Matahari Bunda Kindergarten, Kurun District, Gunung Mas Regency. The results of the study indicate that: 1) Learning planning begins with compiling a one-year activity program. 2) In the division of teaching tasks for teachers, it is adjusted to their respective competencies and expertise by holding a coordination meeting first at the beginning of the new school year. 3) The implementation of learning uses classical learning models, play while learning methods, and thematic. 4) Learning evaluations are also carried out periodically, namely every day, every end of the month and every end of the semester.